Solving Arms Problem Using Differential Transform Method (DTM) - Muhammad Shafiq Aiman Muhammad Faizal,; Noor Azliza Abd Latif, (Enhanced Knowledge in Sciences and Technology, 2024)
This research, a semi analytical solution called differential transform method used to solve arms race model problem. With the help of Maple 2023, the approximate solution of the arms race model equations were obtained. By using this method to the arms race model proved that the computation works can be reduced and save amount of time. The numerical results derived by differential transform method or DTM is compared to the exact solution which included with all the Arms race model equation. The results indicate the efficiency of differential transform method in solving non-linear differential equation depends on the specific characteristic for every equation. Differential transform method success in solving two examples for Arms race model, emphasizing its simplicity in tackling differential problems with minimal computational work.